Mudanças e culturas organizacionais diante de emergências em saúde : impactos e aprendizados da pandemia de covid-19 sob a percepção de profissionais da Atenção Primária à Saúde - Magalhães, Nadine Daniele (2024)
The covid-19 pandemic, which began in 2020, was the driver of countless social, economic, political and cultural changes in the daily lives of populations around the world. With millions of cases accumulated throughout the pandemic period, portraying one of the most challenging health emergencies of the 21st century, in Brazil, the health crisis required quick and efficient actions to avoid the collapse of the Unified Health System (SUS). Public health management, already complex, faced a sudden process of changing work protocols and strategic demands, exacerbating the pressure on health professionals and managers. In this context, the Primary Health Care (APS) network stood out as crucial for preventing injuries and reducing harm, being the main gateway to the health system in municipalities, coordinating comprehensive care and articulating with other levels of care to meet the population's health needs, in addition to helping to avoid unnecessary occupancy of hospital beds. Faced with this scenario of significant changes, the adaptation capacity of organizations is influenced by cultural assumptions shared by their members, determining situations of resistance or resilience to transformations. This panorama also highlights organizational learning processes by demonstrating the occurrence of cycles of reading and interpreting the environment, making decisions and evaluating mistakes and successes, until the incorporation of the latter into the organizational routine, relating to the change and construction of cultural aspects. Thus, the dissertation investigates the impacts of the covid-19 pandemic on public health management in Belo Horizonte, focusing on organizational transformations in the Primary Health Care network. The research focuses on the Belo Horizonte Municipal Health Secretariat (SMSA-BH), seeking to understand how the changes caused by the pandemic were assimilated and incorporated into organizational practices from the perspective of APS professionals, especially those who are part of groups of street-level bureaucrats and mid-level bureaucrats. The objectives of the study include identifying the effects of the pandemic on the routine of the organization's members, changes in organizational practices, the cultural elements that influenced these transformations and the learning consolidated and applied in a new health emergency in the municipality. It also sought to identify cultural similarities and differences between the two groups covered in the research, in order to analyze the possible subcultures present in the organization. The methodology adopted is based on a qualitative and exploratory case study, using data collected through literature review, documentary survey, questionnaires and semistructured interviews, using content analysis to interpret the perceptions of different groups within the institution. Reflections of changes were observed, especially in the level of overload and stress of professionals, in the informatization and management of work processes, in the dynamics of user care in Primary Care and in the forms of communication and integration between teams and levels of activity. Despite a collective cultural identity shared between the research groups focused on the organizational mission of saving lives, there was a distinction in perceptions and interpretations, influenced by cultural elements that relate to the particular characteristics of the levels of bureaucracy in which each group is found. It was also concluded that learning processes occurred in the organization during and after the pandemic, enhanced by greater dialogue, critical reflection and systemic thinking by professionals, resulting in the consolidation of practices that worked. It was possible to verify the application of learning from the pandemic due to the occurrence of a new health emergency during the research, this time concerning arboviruses, with the practices that proved to be efficient in the previous emergency being rescued. Among the limitations of the research, the lack of depth in the perceptions of street-level bureaucrats stands out due to the data collection instrument and the limited time for more detailed interviews. The time that has passed since the beginning and end of the pandemic and the coincidence with the arbovirus epidemic may also have influenced the professionals' perceptions. It is suggested that new studies explore the relationships between change, culture and organizational learning in other contexts, to verify the applicability of the results found and enable comparisons that enrich the understanding of these phenomena in different health organizations.